Ketenangan Jiwa Dan Psychological Well-Being: Studi Pada Santri Mahasiswa Di Pondok Pesantren - Hardi, Nur Fitriyani (Batanang : Jurnal Psikologi, 2022)
Students who migrate and study in Yogyakarta, many live in Islamic boarding schools. The consequence is that they have a dual role, namely the role of a student and the role of an Islamic boarding school student. In addition to study and organizational activities on campus, the obligation that must be carried out is participating in activities at Islamic boarding schools. Academic demands and busy routines are one of the causes of pressure experienced by students. Lack of time management in daily activities due to the role of students as well as students in participating in various activities outside campus such as organizations and others causes psychological pressure, fatigue, decreased interest in learning, irritability, weakened responsibilities, and causes anxiety and depression. The discovery of these problems is the background to the question of how psychological well-being is then associated with peace of mind in the students of the Ulul Albab Islamic Boarding School Balirejo Yogyakarta. This research is quantitative research with a correlation approach method. In this study, as many as 85 samples were taken using a simple random sampling technique after collecting data by distributing questionnaires, then testing the hypothesis using the Pearson product-moment correlation test. The results of the analysis show that there is a significant relationship between mental calm and psychological well-being in the students of the Ulul Albab Balirejo Islamic boarding school in Yogyakarta with a p-value (sig) = 0, 000 < 0.01 and a correlation coefficient (r count) of 0.720. In addition, the two variables have a positive relationship, meaning that the higher the level of psychological well-being, the higher peace of mind in the Ulul Albab Islamic Boarding School Balirejo Yogyakarta students.Keywords: Psychological Well-Being, Peace of Mind, Islamic Boarding School